System feasibility: Designing a chlorine dioxide self-generating package label to improve fresh produce safety part II: Solution casting approach. (June 2018) - Saade, Carol; Annous, Bassam A.; Gualtieri, Anthony J.; Schaich, Karen M.; Liu, LinShu; Yam, Kit L.
Abstract: This work evaluated the ability of an innovative and practical package label made from biobased polymers impregnated with sodium chlorite and citric acid to generate and release chlorine dioxide (ClO2 ) at levels sufficient to inactivate pathogenic bacteria on packaged fresh produce. The concentrations of generated ClO2 by these labels were dependent on the number of layers used and the inclusion of barrier layers. Release rates decreased exponentially with number of layers, providing an additional level of control. Storage temperature had no significant effect on the release of ClO2 . All labels released ClO2 at concentrations capable of complete inactivation of Salmonella cells on TSA plates. Under low-humidity conditions, the labels reduced the levels of Salmonella on inoculated mung bean seeds by up to 2.0 log CFU/g. These results indicate that these labels can be used in a wide range of storage environments for enhancing safety and shelf-life of packaged fresh produce. Industrial relevance: The biobased packaging labels present a commercially viable solution to the problem of controlling microbial growth on fresh produce. Due to the ease of manufacture under existing commercial coating technology, they can be produced and activated simultaneously with fresh produce packaging in the plant. These labels can be adapted to different food safety requirements by modulating the number of functional biobased layers, without or with biobased barrier layers, and label surface areas for generating the required concentration of ClO2 at the optimal rate. Highlights: Self-generating ClO2 biobased labels to protect fresh produce are described. Controlled release of ClO2 is achieved through label design. Labels are activated immediately before use during assembly. Reaction is sustained by moisture released from respiration of fresh produce. Effectiveness against Salmonella is established using TSA plates and mung bean seeds.